Somatic loss of BRCA1 and p53 in mice induces mammary tumors with features of human BRCA1-mutated basal-like breast cancer - Liu, Xiaoling; Holstege, Henne; van der Gulden, Hanneke; Treur-Mulder, Marcelle; Zevenhoven, John; Velds, Arno; Kerkhoven, Ron M; van Vliet, Martin H; Wessels, Lodewyk F A; Peterse, Johannes L; Berns, Anton; Jonkers, Jos (Proceedings of the National Academy of Sciences - PNAS, 2007)
Women carrying germ-line mutations in BRCA1 are strongly predisposed to developing breast cancers with characteristic features also observed in sporadic basal-like breast cancers. They appear as high-grade tumors with high proliferation rates and pushing borders. On the molecular level, they are negative for hormone receptors and ERBB2, display frequent TP53 mutations, and express basal epithelial markers. To study the role of BRCA1 and P53 loss of function in breast cancer development, we generated conditional mouse models with tissue-specific mutation of Brca1 and/or p53 in basal epithelial cells. Somatic loss of both BRCA1 and p53 resulted in the rapid and efficient formation of highly proliferative, poorly differentiated, estrogen receptor-negative mammary carcinomas with pushing borders and increased expression of basal epithelial markers, reminiscent of human basal-like breast cancer. BRCA1- and p53-deficient mouse mammary tumors exhibit dramatic genomic instability, and their molecular signatures resemble those of human BRCA1-mutated breast cancers. Thus, these tumors display important hallmarks of hereditary breast cancers in BRCA1-mutation carriers.